Nellie Bly - Knudsen, Michelle (She persisted (Philomel Books), 2021)
"Nellie Bly was a journalist and one of the first investigative reporters ever. She went undercover to expose wrongdoing and famously raced around the world so she could write about the experience for her newspaper. Reaching for her dreams wasn't easy. But Nellie never gave up, no matter how many obstacles she faced--and she helped others along the way." -- Amazon.com.